Investigation of the Plasmodium falciparum RH5-Interacting Protein (PfRIPR) as a blood-stage malaria vaccine target - Williams, BG (2021)
Malaria is an ancient disease that still affects millions of people in endemic regions. Despite ongoing global efforts to produce a vaccine against the malaria parasite, chiefly Plasmodium falciparum, an effective vaccine is not yet available. In recent years, new highly conserved blood-stage vaccine candidates have emerged including PfRH5, now being investigated in clinical trials. PfRH5 forms the ‘RCR’ complex with two other proteins, PfRIPR and PfCyRPA; this essential and highly conserved complex is critical for merozoite invasion of erythrocytes. Here, PfRIPR is investigated as a potential new blood-stage vaccine candidate. PfRIPR is a large and complex protein containing of 10 EGF-like domains. Antibodies raised against full-length PfRIPR are effective at blocking merozoite invasion of erythrocytes in vitro, however, beyond this our knowledge is sorely lacking. My work shows that the epitopes of neutralising antibodies fall exclusively within a small region of PfRIPR corresponding to EGF-like domains 5-8. I demonstrate that immunisation with PfRIPR EGF (5-8) protein yields a four-fold improvement in antigen-specific IgG quality compared with full-length PfRIPR. In addition, I show that monoclonal antibodies raised against PfRIPR EGF (5-8) can block merozoite invasion of erythrocytes whereas antibodies that bind outside this region do not. Co-immunisation of PfRIPR with either PfRH5, PfCyRPA, or all three proteins has revealed a complex relationship between the antigens. PfRIPR is the most immunodominant of the three antigens but yields the least potent IgG. These experiments also strongly suggest that co-immunisation leads to inter-antigen synergy which improves the potency of the IgG response. This work provides a platform for second-generation PfRIPR vaccines based on PfRIPR EGF (5-8) to be developed and tested in conjunction with PfRH5 and PfCyRPA.